ROLE PLAYING METHOD TO INCLUDE CHARACTERS OF SOCIAL CARE AND EMPATHY IN PANCASILA EDUCATION - Dhian Indriyanawati; Arief Cahyo Utomo (Universitas Majalengka, 2024)
Character education is one part of the personality formation process that must be applied and instilled to improve the quality of the nation. To instill and improve the character through the world of education because it greatly influences each individual to have a good character. One of the characters that is considered important in the learning process is social care and empathy because by having this personality it can be beneficial for everyone in the environment and must be instilled early on through the role-playing method learning process. The aim of this study is to explain the role-playing method's application and its effects on Pancasila Education in fifth-grade at Rejosari State Elementary School in terms of fostering social concern and empathy. This kind of study employs qualitative descriptive research. Teachers and children in fifth-grade at Rejosari State Elementary School served as the study's subjects. In this study, semi-structured interviews, documentation, and observational methods were employed as the data gathering methods. This study employed source and technique triangulation as part of its data validity technique. Data reduction, data visualization, and conclusion drafting are some of the data analysis approaches that are employed. The results of this study indicate that teachers and students of fifth-grade of Rejosari State Elementary School already have quite good social care and empathy characters in the learning process using the role-playing method in Pancasila Education, shown by the attitude of helping each other, comforting friends who are sad, and being able to control anger.